“哈哈(haha)” in WeChat Chinese Conversations - Weiting Yuan (Studies in Applied Linguistics & TESOL, 2025)
Few studies have considered the micro-analysis of written laughter in the digital world in its sequential context (beyond frequency and distribution). The present study fills this gap by examining “transcribed” laughter “哈哈(haha)” in Chinese conversations on WeChat from a conversation analytic perspective. A line-by-line analysis was conducted to identify how speakers use “哈哈(haha)” in different sequences to perform different social actions. This study has shown that the sequential environments of the laughter “哈哈(haha)” in WeChat Chinese conversations can be classified into three types: TCU-initial “哈哈(haha),” TCU-end “哈哈(haha)” and stand-alone “哈哈(haha).” These three types of “哈哈(haha)” perform the actions of mitigating disalignment, managing failure or misconduct, and displaying minimal engagement, respectively. The findings expand the current conversation analysis literature on laughter by describing the use of written laughter in a previously unexamined context and help both native and non-native speakers better navigate informal Chinese digital communication and avoid misunderstandings.